Crystal structure of an L‐type lectin domain from archaea. Issue 4 (9th November 2022) - Khan, Farha; Kaza, Suguna
Abstract: The crystal structures of an L‐type lectin domain from Methanocaldococcus jannaschii in apo and mannose‐bound forms have been determined. A thorough investigation of L‐type lectin domains from several organisms provides insight into the differences in these domains from different kingdoms of life. While the overall fold of the L‐type lectin domain is conserved, differences in the lengths of the carbohydrate‐binding loops and significant variations in the Mn 2+ ‐binding site compared to the Ca 2+ ‐binding site are observed. Furthermore, the sequence and phylogenetic analyses suggest that the archaeal L‐type lectin domain is evolutionarily closer to the plant legume lectins than to its bacterial or animal counterparts. This is the first report of the biochemical, structural, sequence, and phylogenetic analyses of an L‐type lectin domain from archaea and serves to enhance our understanding of the species‐specific differences and evolution of L‐type lectin domains.